2022
DOI: 10.20473/bk.v11i1.37109
|View full text |Cite
|
Sign up to set email alerts
|

Between the Sustainable Development Narrative and the Environmental Crisis

Abstract: This study aims to find out what narratives of sustainable development are dominant and what is limited to the presentation of the contents of elementary school textbooks in Indonesia. This study uses quantitative and descriptive content analysis with an instrument in an analysis sheet based on theory. The data sources are 51 elementary thematic textbooks from grades one to six. The study results show that the concept of sustainable development (SDGs) consists of 17 goals and education for sustainable developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
1
1
1
Order By: Relevance
“…Furthermore, the focus of the textbooks on the social inclusion dimension aligns with the trends observed in various international contexts but also reveals critical gaps. In In-donesia, elementary school textbooks prominently feature economic activities, highlighting a different imbalance where social and environmental themes are less integrated [49]. In contrast, the UAE's fourth-grade science textbooks show a significant gap in the social dimension, indicating an opposite imbalance compared to our findings [50].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the focus of the textbooks on the social inclusion dimension aligns with the trends observed in various international contexts but also reveals critical gaps. In In-donesia, elementary school textbooks prominently feature economic activities, highlighting a different imbalance where social and environmental themes are less integrated [49]. In contrast, the UAE's fourth-grade science textbooks show a significant gap in the social dimension, indicating an opposite imbalance compared to our findings [50].…”
Section: Discussioncontrasting
confidence: 71%
“…However, the representation of economic growth, social inclusion, and environmental protection varies widely. In Indonesia, elementary school textbooks prominently feature economic activities, while Saudi Arabian science textbooks include economic topics without consistently integrating social and environmental themes, indicating a need for a more balanced approach [49]. In the UAE, fourth-grade science textbooks showed that the social dimension was the least frequently represented, highlighting a significant gap [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tantangan lain yang dihadapi adalah krisis lingkungan, yang meliputi perubahan iklim, degradasi lingkungan, dan kehilangan keanekaragaman hayati (Gunansyah, 2022). Dalam upaya mencapai pembangunan ekonomi, seringkali aspek lingkungan tidak diperhitungkan dengan baik.…”
Section: Pendahuluanunclassified